Promoting Critical Thinking and Writing Skills through Problem-Based Learning - Mantra, Ida Bagus Nyoman (Journal on Studies in English Language Teaching (JOSELT), 2024)
Writing is a crucial language skill that must be actively and consistently developed. This study used a brainstorming technique to improve student's writing skills through two cycles of learning activities using a classroom action research design. The primary data for this study were gathered by administering a questionnaire, post-tests, and pre-tests in an EFL classroom. Compared to the pre-test result, the results demonstrated that the student's writing skills had improved dramatically in the first and second learning cycles. As a result, using the brainstorming technique in writing classes is highly beneficial. According to this study, educators should consider implementing the brainstorming technique to help students become better writers.